Richness and Reciprocity - Thomas Harding RN, PhD; Kerry Mawson RN, MHSc (SAGE Publishing, 2017)
Recruiting and retaining nurses in mental health practice settings have long been problematic: A situation which is not helped by student nurses being exposed to negative attitudes about mental health nursing or poor clinical experiences. A pilot program in which student nurses were mentored on the mental health clinical placement was initiated at an Australian School of Nursing. A qualitative study was undertaken to explore the value of this program for the student mentee and the registered nurse mentor. A questionnaire containing six questions was distributed to all participants before and after the clinical experience. The questions were open format seeking data on (a) the perceived advantages or disadvantages of mentoring, (b) perceptions of whether mentoring contributes to professional development, and (c) whether mentoring contributes personally to the participant. The data were subjected to inductive thematic analysis. The registered nurse mentors found that time diverted from clients was a barrier to mentoring students; however, they experienced reciprocity through nurturance of self, students, and the profession. The student mentees found that they experienced a richer and deeper learning environment. Mentoring provides a satisfying learning environment for both parties if carefully implemented and supported.